BEST EMPLOYEE ASSESSMENT DECISION SUPPORT SYSTEM USING ANALYTICAL HIERARCHY PROCESS (AHP) AND ADDITIVE RATIO ASSESSMENT (ARAS) METHODS - Muhammad Rizkiansyah; Yunita Yunita; Nabila Rizky Oktadini (Sriwijaya Journal of Informatics and Applications, 2022)
The purpose of this research is to make it easier to solve the problem of evaluating the best employees in the company PT. ASA KARYA MULTIGUNA, therefore a decision support system is needed. The Analytical Hierarchy Process (AHP) method is used for weighting criteria and the Additive Ratio Assessment (ARAS) method is used for ranking alternatives. From the results of the weighting of the criteria obtained weights for ability (0.31), initiative (0.04), discipline (0.08), performance (0.21), responsibility (0.13), attendance (0.08), communication (0.04), attitude (0.08). From the results of the alternative rankings, for the November 2020 period, the first place was Hendri Gustian, the second was Eka Wingsati Sartono, and the third was Eva Maya Fadila. In the December 2020 period, the first place was Hariyadi, the second was Hendri Gustian, and the third was Deden Kurniawan. In the January 2021 period, the first rank was Deden Kurniawan, the second rank was Hilman Djuniarto, and the third rank was Nurhayati Natalia. From the data for 3 periods from November 2020 to January 2021, which were tested managed to the average confidence level is 84.1%.